Idiomatic Expressions and Their Translation Equivalence into English in the Karo Cultural Legend "Pustaka Sembiring" - Tarigan, Helti Margaretha; Lubis, Syahron; Zein, T. Thyrhaya (Journal La Sociale, 2025)
This study uses a qualitative descriptive method. The source of research data is a legend entitled "Pustaka Sembiring", a Karo language text contained in the book "Himpunan Buku Legenda Karo" pages 171-176 published by the Karo Regency Tourism, Arts and Culture Office in 2007, and its translation by Sehati Mitha Sembiring. The purpose of this study is to identify and classify Karo idiomatic expressions in the text "Pustaka Sembiring" and the equivalence of the meaning of its translation in English. Through data collection and discourse analysis, 56 idiomatic expression data were found, each of which was classified into pure idioms (6 data), semi idioms (28 data), and literal idioms (22 data). In terms of quality of equivalence of meaning, there are 41 equivalent translations (73.2%), 10 equivalent translations (17.9%), and 5 non-equivalent translations (8.9%).